KEMANDIRIAN BELAJAR MAHASISWA PENDIDlKAN TEKNIK MESIN DITINJAU DAR! ASAL SEKOLAH, TEMPAT TINGGAL, DAN LAMA STUDI - Pardjono, Pardjono (Jurnal Cakrawala Pendidikan, 2007)
he system employing semester credit units requires students'good self-regulated learning in order that they attain learning goalssuccessfully. The present article concerns a research aimed atknowing(l) of what level mechanical engineering students' selfdependence in learning was as seen from both their self-stated viewsabout their self-regulated learning and their self-regulated learningin practice; (2) whether there was any difference in levelof selfregulated learning among those having different typesof high schooleducational background; (3) whether there was any differenceinlevel of self-regulated learning among those having studied fordifferent numbersof semesters; and (4) whether the environmentwhere they live influences their self-dependence in learning,or, inother words, their self-regulated learning.The research employed a positivistic approach which wasexploratory in nature. The population consistedof 254 students ofthe Mechanical Engineering Education Study Program, Faculty ofEngineering, State University of Yogyakarta, who were takingcourses in one even-numbered semester or another in the academicyearof 2005/2006. The sample size was 228 and the researchsubjects were randomly selected. The data were compiled by using aclosed self-report typeof questionnaire using a Linkert-type scalemodel. The data were analyzed by meansof non-parametricstatistics using the Kruskal-Wallis Test and the Mann-Whitney UTest since the data distribution did not fulfill the inferentialparametric analysis assumption The research findings indicate that (1) the level of the students'self-regulated learning was very good though the mean score fortheir self-regulated learning in practice is lower than that for theirself-stated views about their self-regulated learning; (2) there is nodifference in levelof self-regulated learning between those with ageneral high school educational background and those with avocational high school educational background, accordingto boththeir self-stated views on it and their self-regulated learning inpractice; (3) there is no difference in levelof self-regulated learningbetween those who live with their family and those who live at someoff-campus housing, accordingto both their self-stated views on itand their self-regulated learning in practice; and (4) there is nodifference in levelof self-regulated learning among those havingstudied for different numbersof semesters, according to both theirself-stated views on it and their self-regulated learningin practice,excluding the viewsof those in their second semester on their selfregulated learning